118k views
0 votes
In order to solve for the variable in the equation Mikel first applies the distributive property. Which equation is a result of this step?

In order to solve for the variable in the equation Mikel first applies the distributive-example-1
User JCollier
by
4.9k points

2 Answers

1 vote

Answer:

The equation is:


1-x-2 + 2x = 10x-25-x

Explanation:

The distributive property says that


c(a+b) = ac + bc

In this case we have the following equation


1-(x+2) + 2x = 5(2x-5)-x

Then apply the distributive property as shown below


1-1*x-1*2 + 2x = 5*2x-5*5-x

Now simplify the expression


1-x-2 + 2x = 10x-25-x

So the equation that results after applying the distributive property is:


1-x-2 + 2x = 10x-25-x

User Eugene Trifonov
by
4.8k points
5 votes

Answer:

1 - x - 2 + 2x = 10x - 25 - x

Explanation:

We have the expression: 1 - (x+2) + 2x = 5(2x - 5) - x

Applying the distributive property we get:

1 - x - 2 + 2x = 10x - 25 - x

So, the following equation is the result of that step: 1 - x - 2 + 2x = 10x - 25 - x

User Abraam Magued
by
5.1k points